# Tarea 2

Valor numérico de expresiones compuestas

Ejercicio 13

Hallar el valor numérico de las expresiones siguientes, para:
1
2
1
a = 1, b = 2, c = 3, d = 4, m = , n = , p = , x = 0
2
3
4
1

(a + b)c − d =

2

(a + b)(b − a) =

3

(b − m)(c − n) + 4a 2 =

4

(2m + 3n)(4 p + b 2 ) =

5

(4m + 8 p )(a 2 + b 2 )(6n − d ) =

6

(c − b)(d − c )(b − a )(m − p ) =

7

b 2 ( c + d ) − a 2 ( m + n) + 2 x =

8

2mx + 6(b 2 + c 2 ) − 4d 2 =

9

 8m 16 p 
+

a =
b 
 9n

10

x + m( a b + d c − c a ) =

11

4(m + p) a 2 + b 2
÷
=
a
c2

12

(2m + 3n + 4 p )(8 p + 6n − 4m)(9n + 20 p) =

13

c 2 (m + n) − d 2 (m + p) + b 2 (n + p) =

14

 c2 + d 2
2 

÷
m=

a
d

15

(4 p + 2b)(18n − 24 p) + 2(8m + 2)(40 p + a ) =

16

2
d
5+ 2

m =
d −b
p2

17

(a + b) c 2 + 8b − m n 2 =

a+

18

 a+c
6n 

+
 2
 ÷ (c + d ) p =
b

19

3(c − b) 32m − 2(d − a) 16 p −

2
=
n

20

6abc
3mn
cdnp
+

=
2 8b 2(b − a ) abc

21

a 2 + b2
+ 3(a + b)(2a + 3b) =
b2 − a 2

22

 1 1  1 1   1 1 
b 2 +  +  +  +  +  =
 a b  b c   n m 

23

(2m + 3n)(4 p + 2c ) − 4m 2n 2 =

24

c
3 − n =
2ab − m b − m

2

b2 −

RESPUESTAS
1

(a + b)c − d =
(1 + 2)3 − 4 = 3 ⋅ 3 − 4 = 9 − 4 = 5

2

(a + b)(b − a) =
(1 + 2)(2 − 1) = 3 ⋅ 1 = 3

(b − m)(c − n) + 4a 2 =
1 
2
21
7
7 + 8 15

 4 − 1  9 − 2 
 3  7 
2
+4= +4=
=
= 7 12
 2 −  3 −  + 4 ⋅ 1 = 

 + 4 =    + 4 =
2
3
2
3
2
3
6
2
2
2





  

3

4

(2m + 3n)(4 p + b 2 ) =
2  1
 1
 2 6  4

2
 2 ⋅ + 3 ⋅  4 ⋅ + 2  =  +  + 4  = (1 + 2)(1 + 4) = 3 ⋅ 5 = 15
3  4
 2
  2 3  4

5

(4m + 8 p )(a 2 + b 2 )(6n − d ) =
1 2
2
 1
 4 8
 12

2 
 4 ⋅ + 8 ⋅  1 + 2  6 ⋅ − 4  =  + (1 + 4 ) − 4  = (2 + 2)(5)(4 − 4 ) = 4 ⋅ 5 ⋅ 0 = 0
4
 2
 3
 2 4
3

(

)

6

(c − b)(d − c )(b − a )(m − p ) =
(3 − 2)(4 − 3)(2 − 1) 1 − 1  = 1⋅1⋅1⋅  2 − 1  = 1
2 4
 4  4

7

b 2 ( c + d ) − a 2 ( m + n) + 2 x =
7 168 − 7 161
5
1 2
3+ 4
22 (3 + 4) − 12  +  + 2 ⋅ 0 = 4 ⋅ 7 − 1
=
= 26
 = 28 − =
6
6
6
6
2 3
 6 

8

2mx + 6(b 2 + c 2 ) − 4d 2 =
1
2 ⋅ ⋅ 0 + 6(2 2 + 32 ) − 4 ⋅ 42 = 6(4 + 9 ) − 4 ⋅ 16 = 6 ⋅ 13 − 64 = 78 − 64 = 14
2

9

10

11

12

 8m 16 p 
+

a =
b 
 9n
1
 8 16 
 1
16 ⋅ 

 8⋅
4  ⋅ 1 =  2 + 4  =  4 + 4  = 2 + 2 = 2 + 6 = 8 = 2 2
 2+
2 
3
3
3
 18 2   6 2  3
9⋅ 2

3
3

x + m( a b + d c − c a ) =
1
1
1
62
0 + (12 + 43 − 31 ) = (1 + 64 − 3) = ⋅ 62 =
= 31
2
2
2
2

4(m + p) a 2 + b 2
÷
=
a
c2
1 1
4 +  2
2
 2 4  ÷ 1 + 2 = 4 2 + 1  ÷ 1 + 4 = 4 ⋅ 3 ÷ 5 = 12 ÷ 5 = 12 ⋅ 9 = 108 = 27 = 5 2

1
32
9
4 9 4 9 4 5 20
5
5
 4 

(2m + 3n + 4 p )(8 p + 6n − 4m)(9n + 20 p) =

2
1  1
2
1  2
1   2 6 4  8 12 4  18 20 
 1
 2 ⋅ + 3 ⋅ + 4 ⋅  8 ⋅ + 6 ⋅ − 4 ⋅  9 ⋅ + 20 ⋅  =  + +  + −  +  =
3
4  4
3
2  3
4   2 3 4  4 3 2  3
4 
 2
(1 + 2 + 1)(2 + 4 − 2)(6 + 5) = 4 ⋅ 4 ⋅ 11 = 176

13

14

15

c 2 (m + n) − d 2 (m + p) + b 2 (n + p) =
7
3
11
1 2
1 1
 2 1 3+ 4
 2 + 1  8 + 3 
32  +  − 4 2  +  + 2 2  +  = 9
 − 16
 + 4
 = 9 ⋅ − 16 ⋅ + 4 =
6
4
12
2 3
2 4
 3 4  6 
 4   12 
63 48 44 21
44 126 − 144 + 44 26
2
1

+
=
− 12 +
=
=
=2 =2
6
4 12 2
12
12
12
12
6
 c2 + d 2
2 

÷
m=

a
d

2
2
 3 +4
2  1  9 + 16 2  1  25  1
1 5
1

⋅ =
÷ ⋅ = 
÷
÷ 1 ⋅ = 5 ⋅ = = 2

1
2 2  1
2 2
2
4 2  1
 2

(4 p + 2b)(18n − 24 p) + 2(8m + 2)(40 p + a ) =
2
1  1
 1

 1 
 4 ⋅ + 2 ⋅ 2 18 ⋅ − 24 ⋅  + 2 8 ⋅ + 2  40 + 1 =
3
4  2
 4

 4 
4
 36 24   8
 40 
 + 4  −  + 2 + 2  + 1 = (1 + 4)(12 − 6) + 2(4 + 2 )(10 + 1) =
4  2
4
 3
 4

(5)(6) + 2(6)(11) = 30 + 2 ⋅ 66 = 30 + 132 = 162

2
d
5+ 2

m =
d −b
p2
2
2
5+
2
5+
1
1
4
 
1+
 2  = 1+ 2 ×
4 = 3 × 5 + 8 = 3 × 13 = 3 ⋅ 208 = 624 = 312

2
1
1
2
2 1 2
2
2
4−2
1
 
6
6
6
4
a+

16

17

(a + b) c 2 + 8b − m n 2 =
1 2
1 2
3
1 45 − 1 44
2
=
= 14
(1 + 2) 3 + 8 ⋅ 2 −
  = 3 ⋅ 9 + 16 − ⋅ = 3 ⋅ 25 − = 3 ⋅ 5 − =
2 3
2 3
6
3
3
3
3
2

2

18

19

20

 a+c
6n 

 2 + b  ÷ (c + d ) p =

2 
12 

6  

 1+ 3
1 2
1  4
3 
3

 2 + 2  ÷ ( 3 + 4) 4 =  2 + 2  ÷ 7 ⋅ 2 =  2 +

7 4
7
2 7
 ÷ = (1 + 1) ÷ = 2 ÷ =
2 7
2
2 2

2
=
n
16 6
32
1 2
1
3(3 − 2) 32 ⋅ − 2(4 − 1) 16 ⋅ − = 3 ⋅ 1 ⋅
− 2⋅3⋅
− = 3 ⋅ 16 − 6 ⋅ 4 − 3 =
4 2
2
4 2
2
3
3 ⋅ 4 − 6 ⋅ 2 − 3 = 12 − 12 − 3 = 12 − 15 = −3
3(c − b) 32m − 2(d − a) 16 p −

6abc
3mn
cdnp
+

=
2 8b 2(b − a ) abc

6 24
1 2
2 1
3⋅ ⋅
3⋅4⋅ ⋅
6
1 2
36
6 ⋅1⋅ 2 ⋅ 3
2 3 −
3 4 =
+
+ 6 − 12 =
+
− =
2⋅4 2 6
1⋅ 2 ⋅ 3
2(2 − 1)
2 16 2(1) 6
2 8⋅2
6 1 1 18 + 12 − 8 30 − 8 22 11
+ − =
=
=
=
8 2 3
24
24
24 12

21

a2 + b2
+ 3(a + b)(2a + 3b) =
b2 − a2
12 + 22
1+ 4
5
5
5 + 216 221
2
+ 3(1 + 2)(2 ⋅ 1 + 3 ⋅ 2) =
+ 3 ⋅ 3(2 + 6) = + 3 ⋅ 3 ⋅ 8 = + 72 =
=
= 73
2
2
2 −1
4 −1
3
3
3
3
3

2

22

 1 1  1 1   1 1 
b 2 +  +  +  +  +  =
 a b  b c   n m 
2

2
1 1
2 + 1  3 + 2   3 2 
1
1
1
1

2
2 +  +  +  +  +  = 4 + 

+ +  =
2  6   2 1 
 1 2  2 3   2 1 

3 2
2

2

5 49 16 + 5 + 49 70 35
1
 3  5   3 + 4 
 15   7 
4 +    + 
=
=
=
=7
 = 4+ +  = 4+ +
4 2
4
4
2
2
 2  6   2 
 12   2 

23

(2m + 3n)(4 p + 2c ) − 4m 2n 2 =

2

2

2  1
 1

1 2
 2 ⋅ + 3 ⋅  4 ⋅ + 2 ⋅ 3  − 4 ⋅     =
3  4
 2

2 3
1 4
16
4
4 189 − 4 185
5
 2 6  4

= 3 ⋅ 7 − = 21 − =
=
= 20
 +  + 6  − 4 ⋅ ⋅ = (1 + 2)(1 + 6) −
4 9
36
9
9
9
9
9
 2 3  4

c
3 − n =
2ab − m b − m
2
2
3
22 −
3 − 3 = 4 −1 − 3 = 3 −
1 4 −1 8 −1
1
1
4−
2−
2 ⋅1⋅ 2 −
2
2
2
2
2
b2 −

24

2
3 = 3 − 4 = 6 − 4 = 54 − 28 = 26
3 7 9 7 9
63
63
2 2